Pengembangan Aplikasi Penjualan Kopi dengan Metode FIFO pada CV. Mandiri Kopi Berbasis Android - Ramadhania, Dwindah; Ommi Alfina (Universitas Methodist Indonesia, 2025)
CV. Mandiri Kopi is a coffee company with a variety of product variants. The company faces a challenge in accurately managing its inventory, particularly ensuring that incoming and outgoing products comply with their expiration dates and arrival dates. This aspect can potentially lead to losses if older products are not promptly sold. To address this issue, this study aims to develop an Android-based coffee sales application that implements the FIFO method in inventory management. The application's main features include recording sales transactions, managing inventory using the FIFO method, recording sales reports, and notifying users of products approaching expiration. Test results indicate that the application can help the company manage product inventory more efficiently, reduce the risk of stockpiling, and make it easier for admins to monitor sales reports. Thus, the Android-based coffee sales application using the FIFO method can improve the effectiveness and accuracy of inventory management at CV. Mandiri Kopi.